2 - Fashion, Learning and Values in Public Management: Reflections on South African and International Experience: 10.4314/ad.v27i2.22163 - Gasper, Des (Africa Development, 2022)
New Public Management (NPM) has shaken up sleepy and self-serving public organisations. But it was spread like a religion: assumed to be modern, relevant and universally superior, despite having relatively little empirical backing. NPM has now lost much of its gloss, as experience of the massive transaction costs of radical reforms and of their often unfulfilled prerequisites mounts. An untried package was sold and bought. This paper looks for lessons. First, it discusses implications for the types of independent thinking and training required for public managers, including methods for thinking critically, caringly and creatively. Second, it takes a case study, a 1990s phenomenon parallel to but rather differ ent from NPM, South Africa's 'New Public Administration Initiative' (NPA1). The NPA1 made the move from rule-following 'administration' to outcomes oriented 'management', abolished the division between white-oriented 'Public Administration' and black-oriented 'Development Administration' and heavily invested in reforming educational infrastructure for public and development management, including for thinking independently, not swallowing packages from abroad. NPA1, however, has had to reflect on its intellectual identity for the longer-term, otherwise it may be sidelined or eaten by competitors, notably plain 'management'. This paper examines this rise of'management' and its threat to 'public' and 'development'. It argues the need to strengthen the 'public' ori entation by promoting a number of dimensions of that concept beyond merely 'State" and State-society interaction, and to keep alternative senses of'develop ment' and 'management' to the fore in order to prevent monopolisation of these terms by the ideas of the corporate world.